Penatalaksanaan Fisioterapi Pada Kasus Post Release Dequervain Tenosinovitis Syndrome Di RSUD Dr Moewardi Surakarta - TRISTIANA, Dewi Larasati; , Arif Pristianto, SSt.FT.,M.Fis (2014)
Background:Dequervain Tenosynovitis Syndrome (DTS) is an inflammation of the APL and EPB tendons thumb area, which marked pain, swelling, and crepitus. Physiotherapy modalities used are IR and TENS to reduce pain. US reduces muscle spasm, TL with active exercise increases muscle strength, and stretching exercise increases LGS on the thumb. Purpose:To determine the implementation of physiotherapy in reducing pain, reducing muscle spasms, increase muscle strength, and add LGS cases of post release DTS using IR modalities, TENS, US, and TL. Results: after therapy 6 times obtained results, silent pain T0: 20 mm to T6: 3.5 mm, tenderness T0: 40 mm to T6: 19 mm, extension motion pain T0: 50 mm to 28 mm, pain motion abduction T0: 48 mm to T6: 30 mm, and the pain adduction moment T0: 32 mm to T6: 4.5 mm. Reduction of muscle spasm T0: grades 1 to T6: Increased value 0. thumb flexor muscle strength T0: 4+ be T6: 5, thumb extensor T0: 2 to T6: 3+, thumb abductor T0: 2 to 3+ and thumb adductor T0: 3+ into T6: 4+. Improved active LGS thumb F: T0: 100-00-50, becoming T6: 330-00- 150, S: T0: 100-00-00, becoming T6: 350-00-00, LGS passive thumb F: T0 : 120-00-80, becoming T6: 400-00-150, S: T0: 150-00-00, becoming T6: 380-00-00.Conclusion: IR, TENS in the case of post-release DTS can reduce the pain, theUS reduce spasm, active exercise increases muscle strength, and stretching exercise increases LGS.